Case Report: First attempt by off-label use of tenecteplase to treat acute extensive portal venous system thrombosis - Qianqian Li; Ying Piao; Yongguo Zhang; Xingshun Qi (Frontiers in Cardiovascular Medicine, 2024)
Acute extensive portal venous system thrombosis (PVST) can cause lethal complications. Herein, we have for the first time reported the use of anticoagulation combined with systemic thrombolysis by tenecteplase in a male patient with a diagnosis of acute extensive PVST but without liver cirrhosis. After thrombolytic therapy, abdominal pain obviously alleviated. However, urinary bleeding developed, which was reversible by stopping thrombolytic drugs. Finally, this case developed cavernous transformation of the portal vein without portal venous recanalization. In future, the efficacy and safety of tenecteplase should be explored in acute extensive PVST cases.